Activation of the Peroxisome Proliferator–Activated Receptor γ Coactivator 1β/NFATc1 Pathway in Circulating Osteoclast Precursors Associated With Bone Destruction in Rheumatoid Arthritis. Issue 8 (3rd July 2019) - Ma, Jian‐Da; Jing, Jun; Wang, Jun‐Wei; Mo, Ying‐Qian; Li, Qian‐Hua; Lin, Jian‐Zi; Chen, Le‐Feng; Shao, Lan; Miossec, Pierre; Dai, Lie
Abstract : Objective: Activation of osteoclastogenesis at the bone site in rheumatoid arthritis (RA) is well established. The mechanisms by which circulating osteoclast precursors contribute are still unclear. Peroxisome proliferator–activated receptor γ coactivator 1β (PGC‐1β) is implicated in transcriptional regulation of osteoclastogenesis in mouse models. This study was undertaken to investigate the contribution of PGC‐1β to circulating osteoclast precursors and its link to bone destruction in RA. Methods: PGC‐1β expression in RA peripheral blood CD14+ monocytes was increased and showed correlation with joint destruction shown on radiographs. Cells from RA patients or healthy controls were transfected with a lentivirus vector for PGC‐1β gene silencing or overexpression and cultured with macrophage colony‐stimulating factor and RANKL. Bone resorption activity, bone‐degrading enzymes, and signaling molecules were measured in these mature osteoclasts. Results: Increased nuclear accumulation of PGC‐1β was observed in RA peripheral blood CD14+ monocytes, and these cells had stronger osteoclastogenesis than in healthy controls. PGC‐1β protein expression was positively correlated with radiographic joint destruction (r = 0.396–0.413; all P < 0.05). PGC‐1β knockdown suppressed (51–82% reduction) the expression of cathepsin K, tartrate‐resistant acid phosphatase (TRAP), and matrix metalloproteinase 9 (MMP‐9), as well as osteoclast differentiation and bone resorption activity. Conversely, PGC‐1β overexpression increased these markers (by 1.5–1.8‐fold) and osteoclastogenesis. VIVIT, an inhibitor of NFATc1 activation, inhibited the effect of overexpressed PGC‐1β by reducing cathepsin K, TRAP, and MMP‐9 expression. Chromatin immunoprecipitation assay and dual‐luciferase reporter gene assay showed PGC‐1β bound to NFATc1 promoter, leading to transcriptional activation. Conclusion: Activation of the PGC‐1β/NFATc1 pathway in circulating osteoclast precursors was associated with bone destruction in RA. This may represent a new treatment target.